DYNAMICS OF INDICATORS OF THE ENDOTHELIUM MORPHOFUNCTIONAL STATE OF THE BRAIN MICROCIRCULATORY BED VESSELS IN RATS WITH NITRITE-INDUCED ALZHEIMER'S TYPE DEMENTIA ON THE BACKGROUND OF MESENCHYMAL STEM CELL ADMINISTRATION OR WITHOUT IT: DYNAMICS OF INDICATORS OF THE ENDOTHELIUM - Zorenko, Yevgeniya (Medicinski časopis, 2021)
Objective. The aim of this study was to assess the vascular endothelium morphofunctional state of the brain microcirculatory bed in rats with nitrite-induced Alzheimer's type dementia on the background of stem cells administration or without it.Methods. 14 days after the experiment end, the endothelin-1, VEGF-A, eNOS, von Willebrand factor were determined in blood serum by the enzyme immunoassay and photometric methods in rats with a model of nitrite-induced dementia (14 and 28 days of sodium nitrite intraperitoneal introduction) with and without mesenchymal stem cells (MSCs) administration. The brain slices were stained according to the Einarson’s method and immunohistochemically by staging the reaction with antibodies to VEGF.Results. With an increase in the sodium nitrite administration period, the damage degree of brain capillaries and neurons increases, dystrophy of “surviving” neurons develops and ability to produce VEGF decreases. After 14 days of "regeneration period" in groups without  MSCs administration, further stimulation of VEGF production by endotheliocytes, cortex and hippocampus neurons  of varying degrees is observed. In groups where stem cells were introduced, the number of capillaries increases, with endothelial hyperplasia in some places.Conclusion. In animals with nitrite-induced dementia, dose-dependent damage to the endothelium of the capillary bed is noted. From the first day damage the vascular regeneration can be proved by VEGF expression. The stem cells administration more effectively stimulates capillary regeneration, as evidenced by a noticeable increase of the brain capillaries number.